Historical ablation rates on south-east Greenland glaciers measured in the 1933 warm summer. Issue 1 (1st January 2016) - Hasholt, Bent; van As, Dirk; Knudsen, Niels Tvis
Abstract : Ice ablation rates measured on four glaciers in south-east Greenland in summer 1933 are recovered from an old field book of geologist K. Milthers. These unpublished ablation data are among the first measured in Greenland and were obtained during a warm period comparable to that of recent years. Ablation rates of up to 45 mm ice eq. d −1 were observed. Using the Tasiilaq meteorological record, we calculate degree-day factors of ca. 3–5 mm ice eq. d −1 °C −1 . Comparing these results with 1996–2012 observations at one of Milthers' glaciers (Mittivakkat), we find that ablation rates and degree-day factors are significantly higher (61±50%) in recent years. We speculate this to be due to a reduction in surface albedo, and perhaps the retreat of the glaciers out of the cold maritime inversion layer. Our findings suggest that using a temperature-index method that assumes constant degree-day factors may produce inaccurate long-term ablation estimates for south-east Greenland glaciers, further emphasizing the value of the rare 1933 measurements for validation of ablation models.